ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI ANGGREK DI KOTA DENPASAR - Diatmika, I Nyoman; Setiawina, I Nyoman Djinar; Djayastra, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.10.TAHUN 2016, 2016)
Denpasar Bali especially as other areas is also a great opportunity to develop agribusiness orchid. With the condition of agricultural land is limited and narrowed, due to land conversion into non agriculture, it is necessary to further streamline the breakthrough for the use of yard area with the development of orchids. Orchid agribusiness development opportunities is a challenge thatrequires good handling of thought and action of shapes and patterns that can support the development of agriculture and tourism. It is necessary to analyze analyze the influence of labor, land, capital, and skills of farmers to household income horticultural farmers in Denpasar through floriculture production number (Ornamental Plants). To conduct an analysis of its intended purpose, the data collected from 108 farmers orchid, using questionnaires. Furthermore, the data were analyzed using descriptive analysis and path analysis. Results of hypothesis testing is done with path analysis showed that the number of workers a significant negative effect on household income horticultural farmers in Denpasar. Land area, working capital, and total production of positive and significant impact on household income horticultural farmers in Denpasar. While working skills had no significant effect on household income horticultural farmers in Denpasar.  Based on the results of hypothesis testing it was suggested that the need for a standard in the use of factors of production so that farmers can produce optimal production and can obtain the maximum benefit with lower production costs to a minimum.
Keywords: labor, land, capital, skilled farmers, the amount of production, farmers' income.